A new class of entropy stabilized oxides: Commensurately modulated A6B2O17 (A = Zr, Hf; B = Nb, Ta) structures. (November 2021) - Voskanyan, Albert A.; Lilova, Kristina; McCormack, Scott J.; Kriven, Waltraud M.; Navrotsky, Alexandra
Abstract: High entropy oxides (HEOs) have experienced a meteoric rise in the past decade. Here, we report a new class of entropy stabilized A6 B2 O17 (A = Zr, Hf; B = Nb, Ta) oxides whose enthalpies of formation have been determined by high temperature oxide melt solution calorimetry. All four compounds have endothermic enthalpies of formation from binary oxides (AO2 and B2 O5 ), indicating that these modulated phases are entropy stabilized. The unfavorable energetics of formation are counterbalanced by large configurational entropy arising from cation disorder. The calculated configurational entropy per formula unit for A6 B2 O17 is 4.50R J/mol⋅K, which is ~2.8 times higher than the maximum configurational entropy value of 1.61R for an equimolar five cation containing "high entropy oxide". Based on X-ray and neutron diffraction data, measured enthalpies of formation and calculated configurational entropies, one can infer that all four compounds have a high degree of disorder. Graphical abstract: Image, graphical abstract